The relation of traumatic childhood experiences with psychological symptoms and self-esteem in physical education and sport students - Azize Atlı Ozbas; Mehmet Kocak; Nermin Gurhan (Türk Spor ve Egzersiz Dergisi)
This study was performed as a descriptive study to identify the relationship of self-esteem of the students of physical education and sport department with childhood traumatic experience and psychological symptoms. The students joined the activity of 'Turkey Kocfest” Sport Games comprised the universe of this study. A hundred and five students who agreed participating in the study and filled in the data collection forms fully were recruited the study. Data were collected by using the Student Information Form, Childhood Trauma Questionnaire, Brief Symptom Inventory and Self-Esteem Scale. ANOVA (F) t Test and the Correlation Test were used for data evaluation as well as Mann-Whitney U Test which is a non-parametric test. The average ages of the students was 22.38 (SD=3.48) and 58.1 % of them were male. The self-esteem scores of the students were found not to be associated with the socio-demographic variables while the scores were found associated with childhood abuse experience. In addition both the self-esteem scores and childhood abuse experience scores were found associated with the psychological symptoms of students. There was strong negative relationship between emotional abuse (r=0.45; lt;0.01), physical abuse (r=-.33; lt;0.01) and sexual abuse scores of students with self-esteem scores (r=0.3; lt;0.01). Furthermore, a strong negative correlation was detected between all psychological symptoms and self-esteem [somatization (r=-.48; lt;0.01), obsessive compulsive disorder (r=-.47; lt;0.01), personal sensitivity (r=-.50; lt;0.01), anxiety disorder (r=-.50; lt;0.01), depression (r=-.49; lt;0,01), hostility /r=0.41; lt;0.01), phobic anxiety (r=0.49; lt;0.01), paranoid thoughts (r=0.51; lt;0.01), psychoticism (r=.051; lt;0.01), additional topic (r=-.41; lt;0.01)]. Self-esteem is a concept which is necessary to deal with absolutely for improving the quality of life of students and supporting them to resume successful lives through the various dimensions of the life. Childhood experiences should not been disregarded when conducting studies devoted to improve the self-esteem of students; attention should be paid to this issue certainly.